Pengaruh Konsep Diri Terhadap Coping Stress Siswa Kelas X di Sekolah Menengah Atas - Hendini, Annisa; Nuraini, Nuraini (Al-Ittizaan: Jurnal Bimbingan Konseling Islam, 2025)
This study aims to examine the influence of self-concept on coping stress among tenth-grade students at SMAN 42 Jakarta. Employing a quantitative associative approach, data were collected from 70 students selected through simple random sampling from a population of 281. Measurement instruments utilized Guttman scale questionnaires on two variables: self-concept and coping stress. Data analysis using simple linear regression with SPSS version 23 revealed a significant influence of self-concept on coping stress (p < 0.05). The findings indicate that students with a more positive self-concept tend to employ more adaptive coping strategies. These results highlight the importance of self-concept development in enhancing students’ psychological resilience, suggesting implications for school-based counseling interventions to foster healthy self-perception and stress management skills.